Establishment and validation of HPLC methods for the determination of folic acid and parabens antimicrobial agents on folic acid oral solution - Wenhong Wu; Ying Liang; Renbang Zhao; Yude Shi; Jiahui Hou; Jiumei Peng; Jiadi Pan; Xiaoyi Li; Jingjing Zhou (BMC Chemistry)
Abstract Background As the common antibacterial drugs in folic acid oral liquid, parabens are listed as mandatory substances in the quality standard. Both the Chinese Pharmacopoeia and the United States Pharmacopoeia use high performance liquid chromatography for the determination of folic acid, but the quantitative methods of parabens are different. Pharmacopoeias use different instruments to quantify folic acid and parabens, resulting in cumbersome and cumbersome detection methods. Objective Without changing the type of instrument and mobile phase, two methods were established for the determination of folic acid and parabens (methyl paraben; ethyl paraben; propyl paraben) using respective wavelengths and flow comparisons Propyl benzoate) high performance liquid chromatography method. Method Chromatographic separation was achieved on an Agilent 5 TC-C18 HPLC column (5 μm; 250 μm × 4.6 mm) maintained at 25 °C (column temperature). The mobile phase consisted of phosphate buffer (pH 4.0)-methanol. When the ratio is 99:1, it is used to determine the content of folic acid, and when the ratio is 79:21, it is used to determine the content of antimicrobial agents. The flow rate used was 1.2 mL/min, the injection volume of folic acid was 20 µL, and the injection volume of bacteriostatic agent was 50 µL. In addition, the blue applicability grade index (BAGI) and analytical greenness (AGREE) metric tools were used to evaluate the greenness and environmental friendliness of the developed methods. Results The method has a good linear relationship with R2 ≥ 0.9995, the average recovery rate of the two methods is ≥ 95%, and the relative standard deviation (RSD%) accuracy is less than 0.21%. The BAGI tool characterizes the developed method as green. The AGREE score is around 0.5, and the method is also largely consistent with the principles of green analytical chemistry. Conclusions The HPLC method was established for the rapid determination of folic acid and antibacterial agent of parabens in folic acid. The method has high accuracy, strong specificity, high recovery rate, good stability and environmental friendliness. Compared with the method in the pharmacopoeia, it has strong resistance to complex matrix interference, greatly shortens the detection time, and has little damage to the instrument and chromatographic column. It can be used for the quality standard of folic acid oral liquid.